2021
DOI: 10.3390/biomedicines9040357
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Natural Compounds as P-Glycoprotein Inhibitors against Multidrug Resistance

Abstract: Multidrug resistance (MDR) is a common problem when fighting cancer with chemotherapy. P-glycoprotein (P-gp, or MDR1) is an active pump responsible for the efflux of xenobiotics out of the cell, including anti-cancer drugs. It is a validated target against MDR. No crystal structure of the human P-gp is available to date, and only recently several cryo-EM structures have been solved. In this paper, we present a comprehensive computational approach that includes constructing the full-length three-dimensional str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 84 publications
0
20
0
Order By: Relevance
“…Some natural products extracted from plants, have been studied for their modulatory properties on P-gp in the form of alkaloids, flavonoids and phenolics, coumarins, resins, peptides, saponins, terpenoids, and miscellaneous other chemical species [ 8 , 43 , 44 ]. In vitro evidence has shown that some natural products, such as curcuminoids, ursolic and oleanolic acid, and essential oils, can counteract the phenomena of drug resistance in tumor models of innate and acquired resistance such as triple negative breast cancer, hepatocellular carcinoma, and acute myeloid leukemia [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. In this context, a recent paper has shown how essential oils are able to bypass multidrug resistance through different mechanisms all converging towards the inhibition of P-gp.…”
Section: Discussionmentioning
confidence: 99%
“…Some natural products extracted from plants, have been studied for their modulatory properties on P-gp in the form of alkaloids, flavonoids and phenolics, coumarins, resins, peptides, saponins, terpenoids, and miscellaneous other chemical species [ 8 , 43 , 44 ]. In vitro evidence has shown that some natural products, such as curcuminoids, ursolic and oleanolic acid, and essential oils, can counteract the phenomena of drug resistance in tumor models of innate and acquired resistance such as triple negative breast cancer, hepatocellular carcinoma, and acute myeloid leukemia [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. In this context, a recent paper has shown how essential oils are able to bypass multidrug resistance through different mechanisms all converging towards the inhibition of P-gp.…”
Section: Discussionmentioning
confidence: 99%
“…TG1 was derived from THSG deglucosylation, and it has a chemical structure with multiple hydroxyl groups. Previous study indicated that hydrogen bonds were formed between the hydroxyl groups of inhibitors and the R site of drug efflux pump, P-gp [ 27 ]. Thus, the modification of THSG may have improved the reduction of drug efflux effect via P-gp.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many researches were investigated resveratrol as a P-gp inhibitor on cancer cells overexpressing P-gp [ 42 44 ]. Since TG1 has similar chemical structure with resveratrol, and the potential P-gp inhibitor could be predicted by structure [ 27 ]. TG1 might be a P-gp inhibitor to modulate DTX/DOX resistance effects, but it needs more investigation in the future.…”
Section: Discussionmentioning
confidence: 99%
“…We have also previously developed a human mAb targeting the C-terminal domain (CTD) of PCSK9 utilizing phage display-based strategy [ 29 ]. Molecular modeling and docking techniques are widely used to predict the binding mode of a drug with its protein target [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%